2018
DOI: 10.1007/s11084-018-9559-4
|View full text |Cite
|
Sign up to set email alerts
|

The Standard Genetic Code can Evolve from a Two-Letter GC Code Without Information Loss or Costly Reassignments

Abstract: It is widely agreed that the standard genetic code must have been preceded by a simpler code that encoded fewer amino acids. How this simpler code could have expanded into the standard genetic code is not well understood because most changes to the code are costly. Taking inspiration from the recently synthesized six-letter code, we propose a novel hypothesis: the initial genetic code consisted of only two letters, G and C, and then expanded the number of available codons via the introduction of an additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…It was recently shown that the standard genetic code can evolve from a two-letter GC code without information loss or costly reassignments (Frank and Froese, 2018). An expanded (e. g. quadruplet) codons can be thought of in the context of expanding the existing genetic code (Chen & Schindlinger, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the standard genetic code can evolve from a two-letter GC code without information loss or costly reassignments (Frank and Froese, 2018). An expanded (e. g. quadruplet) codons can be thought of in the context of expanding the existing genetic code (Chen & Schindlinger, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches have been much criticized and abandoned. The central argument is that the reading frame with dinucleotides is incompatible with the reading frame with trinucleotides, leading to gene sequences unreadable, problem synthesized shortly with the following sentence "letters belonging to the first position of the next codon would be consistently misread as being the last letter of the preceding codon" (Frank and Froese, 2018). We prove in this paper the existence of mixed circular codes, in particular of dinucleotides and trinucleotides.…”
Section: Discussionmentioning
confidence: 82%
“…Genetic information is molecular memory recorded by triplet codon, but its origin has been investigated and debated for a long time (e.g., [1,2,3,4,5]. It is a miracle of nature that a set of genetic codes was able to produce tens of millions of different species on the earth.…”
Section: Introductionmentioning
confidence: 99%